Changing Behavioral Patterns Related to Maternity and Childbirth in Rural and Poor Populations: A Critical Review. (17th May 2019) - Garcia-Prado, Ariadna
Abstract: While life expectancy has increased worldwide in recent decades, dramatic health inequalities persist across and within countries and between different population groups. Maternal mortality in low- and middle-income countries is almost fifty times that of high-income countries, while neonatal mortality is nine times higher, and both are consistently higher in rural, poor, and indigenous populations. Despite important efforts to expand the supply of health services to disadvantaged populations, these inequalities have not fallen as expected. As a result, more emphasis is now being placed on demand strategies in an effort to change behavioral patterns related to maternity and childbirth. This review surveys the experimental and quasi-experimental literature in the area of maternal and neonatal health in rural and poor areas of developing countries to identify strategies that are capable of modifying demand behavior and thereby impacting key indicators. We analyze three kinds of strategies: those covering direct costs, promotion of social and cultural changes, and introduction of incentives. We find significant results from the combination of individual counselling and women groups in the community, as well as from the introduction of small incentives as opposed to more expensive Cash Conditional Transfers (CCTs). We conclude with lessons for impact evaluation and policy-making.